Chondrichthyian biodiversity in the state of Espírito Santo, Brazil - Santander-Neto, Jones; Lírio, Guilherme Dos Santos; Moreira, José Victor Calenzani De Oliveira; Gadig, Otto Bismarck Fazzano [UNESP]; Hostim-Silva, Maurício (Cambridge University Press (CUP), 2024)
Little is known about the Chondrichthyes fauna of the state of Espírito Santo, southeastern Brazil, notably on the species composition, distribution, and biology. Historically, only a few studies have focused on these issues. Basic taxonomy is one of the main tools employed in cataloguing, organizing, and initiating other, more specific, assessments regarding regional diversity. In this context, this study presents the most comprehensive list of shark and ray species occurring in the state of Espírito Santo to date. The compiled data were obtained from specimens deposited in ichthyological collections, literature reviews, and samplings conducted at fisheries landings and onboard commercial fleet vessels. The findings indicate 79 species, comprising 51 sharks and 28 rays. A total of 53.2% of threatened Brazilian marine elasmobranch species occur in the area, indicating the importance of carrying out local studies focusing on this group. A first record for the Brazilian large-eyed stingray, Hypanus marianae, was also observed for the state, increasing the southern limit of the species known distribution, previously considered restricted to the North and Northeast coasts.
Keywords: distribution; diversity; new record; Rrys; sharks